Myositis autoantibodies in a racially diverse population of children with idiopathic inflammatory myopathies - Megan Mariko Perron; Natalia Vasquez-Canizares; Gabriel Tarshish; Dawn M. Wahezi (Pediatric Rheumatology Online Journal, 2021)
Abstract Background Juvenile idiopathic inflammatory myopathies (JIIMs) is a group of autoimmune disorders, including juvenile dermatomyositis (JDM), juvenile polymyositis (JPM) and overlap myositis, that are characterized by proximal muscle weakness, elevated levels of serum muscle enzymes, and pathognomonic skin findings. While the exact etiology of JIIMs is unclear, the presence of myositis specific autoantibodies (MSAs) have been associated with certain clinical phenotypes, organ involvement and disease prognosis. To date, there have been few studies of the associations between MSA presence and patient ethnicity. It is important to understand the extent to which ethnicity impacts disease manifestations, organ involvement and clinical outcomes. The goal of our study is to determine MSA and myositis associated autoantibody (MAA) presence, clinical phenotype, and disease course in a racially diverse population of pediatric patients with JIIMs. Methods Patients age 2–21 years with a prior diagnosis of JDM, JPM or overlap myositis, who had been tested for MSA/MAA, were eligible for study inclusion. Clinical and laboratory data were collected retrospectively via manual chart review in this single-center study. Descriptive statistics were performed to summarize each variable. Given the small sample size, non-parametric testing was performed using Fischer’s exact test, Wilcoxon rank sum test and Kruskal-Wallis test. Results Thirty one patients were included in the analysis. Race and ethnicity were self-reported as Hispanic (48.4%), white (25.8%), and Black (25.8%). The most prevalent MSAs were anti-MDA5 (25.8%), anti-p155/140 (22.6%) and anti-MJ (19.4%). Presence of autoantibodies (p = 0.04) and pulmonary disease (p = 0.03) were significantly higher in patients of Black or Hispanic descent compared with white descent. Anti-MDA5 antibodies, cutaneous ulceration, cardiopulmonary involvement, hospitalizations and one death were only reported in patients with Black or Hispanic descent. Patients with anti-MDA5 antibodies were more likely to be male (p = 0.04) and to have cutaneous ulceration (p = 0.02). Conclusions This study describes the prevalence of MSA/MAA in a racially diverse group of patients with JIIM and further delineates clinical phenotype and disease complications in these groups. We found a relatively high proportion of children with anti-MDA5 antibodies and described potentially worse clinical courses in children of Black or Hispanic descent. Further investigation is warranted to examine these findings.